Liver lesions in bleak (Alburnus alburnus alborella Filippi) collected from some contaminated sites of Lake Ohrid - Roganović-Zafirova, Danica; Jordanova, Maja (Macedonian Journal of Ecology and Environment, 1999)
Histopathological changes observed in the liver of bleak individuals collected from contaminated sites of Lake Ohrid were presented in this study. The possible correlation of these findings with the pollution-induced hepatic lesions in bleak was discussed. Particular attention was paid to the foci of cell alteration (FCA), tumor-like changes, and coagulative necrosis present in the investigated bleak liver tissue.